Intervention Effect Between Smartphone and the Knowledge in Chronic Obstructive Pulmonary Disease Patients at Prof Chairuddin Panusunan Lubis General Hospital - Tarigan, Amira Permatasari; Pradana, Andika; Rhinsilva, Ella; Ramadhani, Adini Arifah; Sihombing, Benny; Monica, Nanda Soraya; Vera, Yeni (SCRIPTA SCORE Scientific Medical Journal, 2024)
Background: Health applications can assist in managing chronic patients such as Chronic Obstructive Pulmonary Disease (COPD). A smartphone application â€œParu Sehatâ€ is expected to help COPD patients increase their knowledge about the disease and its treatment. Objective: This study aims to examine the benefits of smartphone applications â€œParu Sehatâ€ on the level of knowledge of patients with the COPD about the disease and its treatment. Methods: A quasi-experimental studies were conducted in outpatient of stable COPD patients at Pulmonology and Respiratory Medicine Universitas Sumatera Utara Hospital. This research was conducted from March to June 2022. A questionnaire which elaborated question about COPD and its treatment were used to evaluate the level of knowledge of participants before and after 3 months of using smartphone application â€œParu Sehatâ€. Results: From a sample of 38 COPD patients, the average knowledge level of COPD patients before using the â€œParu Sehatâ€ application as 5.125; after using the smartphone application, it was 8.5625. The hypothesis test shows that the value of p = 0.000, indicating an increase in the level of knowledge about COPD and its treatment. Out of 38 patients, all research subjects were male with the most age being 60 to 70 years old, having a history of heavy smoking and the highest level of severity of COPD 2. Conclusion: â€œParu Sehatâ€ application can influence the knowledge of COPD patients about their illness and treatment as well as the patient's independence in dealing with their illness. Keyword: COPD, level of patient knowledge, smarthphone application Latar Belakang: Aplikasi kesehatan dapat membantu dalam menangani pasien kronis seperti Penyakit Paru Obstruktif Kronik (PPOK). Aplikasi smartphone â€œParu Sehatâ€ diharapkan dapat membantu pasien PPOK meningkatkan pengetahuannya tentang penyakit dan pengobatannya. Tujuan: Penelitian ini bertujuan untuk menilai manfaat dari aplikasi smartphone â€œParu Sehatâ€ untuk tingkat pengetahuan pasien PPOK mengenai penyakit dan pengobatannya. Â Metode: Penelitian quasi eksperimental dilakukan pada pasien PPOK stabil rawat jalan di Pulmonologi dan Kedokteran Respirasi Rumah Sakit Universitas Sumatera Utara. Penelitian ini dilakukan antara bulan Maret 2022 hingga Juni 2022. Kuesioner yang berisi pertanyaan tentang PPOK dan pengobatannya digunakan untuk mengevaluasi tingkat pengetahuan peserta sebelum dan sesudah 3 bulan menggunakan aplikasi smartphone â€œParu Sehatâ€. Hasil: Dari sampel 38 pasien PPOK, rata-rata tingkat pengetahuan pasien PPOK sebelum menggunakan aplikasi smartphone â€œParu Sehatâ€ adalah 5,125; setelah menggunakan aplikasi smartphone menjadi 8.5625. Uji hipotesis menunjukkan nilai p = 0,000 yang menunjukkan adanya peningkatan tingkat pengetahuan tentang PPOK dan pengobatannya. Dari 38 pasien, seluruh subjek penelitian berjenis kelamin laki-laki dengan usia terbanyak yaitu 60 hingga 70 tahun, memiliki riwayat perokok berat dan tingkat keparahan PPOK 2 tertinggi (GOLD 2). Kesimpulan: Aplikasi â€œParu Sehatâ€ dapat mempengaruhi pengetahuan pasien PPOK tentang penyakitnya dan pengobatannya serta kemandirian pasien dalam menghadapi penyakitnya. Kata Kunci: Aplikasi smartphone, PPOK, tingkat pengetahuan pasien